Aplicações da função Wq de Lambert-Tsallis e da disentropia em distribuição quântica chaves - Andrade, Joacir Soares de (2024)
This work is about quantum key distribution and it is divided into theoretical and experimental parts. In the theoretical part, the Lambert-Tsallis Wq function is used to find the analytical formula for the channel’s length that maximizes the secure bit transmission rate in an optical network with classical and quantum signals in the same optical fiber, using different wavelengths, and taking into account the spontaneous Raman scattering. Following, Wq is used to calculate the fluctuation of carriers in a SiO2 integrated amplitude modulator used in continuous variable QKD, as well as in the calculation of the parameter that models a stochastic quantum channel with transmissivity with uniform distribution. At last, a new quantum key distribution protocol, named disentropy-based QKD, is proposed. This protocol uses only amplitude modulation and it detects the eavesdropping action by calculating the disentropy. It is the first QKD protocol that does not use quantum error rate to detect the eavesdropping and it is also the QKD protocol with the simplest implementation ever proposed. In the experimental part, the experimental results of a remotely controlled single-photon detector are presented.